One and all the logic of Chinese sovereignty - Pang, Laikwan (Stanford University Press, 2024)
"The concept of sovereignty is a crucial foundation of the current world order. Regardless of their political ideologies no states can operate without claiming and justifying their sovereign power. The People's Republic of China (PRC) - one of the single most powerful states in contemporary global politics - has been resorting to the logic of sovereignty to respond to many external and internal challenges, from territorial rights disputes to the Covid-19 pandemic. In this book, Pang Laikwan analyzes the historical roots of Chinese sovereignty. Surveying the four different political structures of modern China - imperial, republican, socialist, and post-socialist - and the dramatic ruptures between them, Pang argues that the ruling regime's sovereign anxiety cuts across the long twentieth century in China, providing a strong throughline for the state-society relations during moments of intense political instability. Focusing on political theory and cultural history, the book demonstrates how concepts such as popular sovereignty, territorial sovereignty, and economic sovereignty were constructed, and how sovereign power in China was both legitimized and subverted at various times by intellectuals and the ordinary people through a variety of media from painting and literature to internet-based memes. With the possibility of a new Cold War looming large, globalization disintegrating, and populism on the rise, Pang provides a timely reevaluation of the logic of sovereignty in China as power, discourse, and a basis for governance"-- Provided by publisher.